Influence of different oxide thicknesses on the friction induced and continuous solid-state recycling of aluminum scrap - Gabsa, Steffen; Homberg, Werner; Goller, Timothy; Nordieker, Ansgar Bernhard; Grundmeier, Guido (Materials Research Proceedings)
Abstract. Saving emissions and a circular economy are key aspects of sustainable production and compliance global climate change targets. Friction-induced solid-state recycling of aluminum scrap to production endless semi-finished products. Scrap is fed into a continuously rotating wheel. This requires less energy compared to heat-based recycling processes. Different sizes, shapes and surfaces of chips can be used as starting material in the process. The influence of this has been shown in past publications. A native oxide layer is a fixed component of aluminum surface. This layer is broken up during the forming process, allowing the aluminum to bond. In addition to the geometry, the surface finishes and the thickness of the oxide layer are therefore also important input variables in friction-induced solid-state recycling. The oxide layers on the chips were determined for the investigation. In addition, different layer thicknesses were produced to survey their influence. The resulting semi-finished products were evaluated on the basis of their tensile strength and microstructure. The main result of the investigations is the fact that semi-finished products made from chips with thicker oxide layers tend to be more brittle. In addition, thick oxide layers cause microstructural and surface defects.

Additive manufacturing of polymeric pressure die for rotary draw bending process - Kaleem, Muhammad Ali; Steinheimer, Rainer; Frohn-Sörensen, Peter; Gabsa, Steffen; Engel, Bernd (The International Journal of Advanced Manufacturing Technology)
Abstract 3D printing or additive manufacturing (AM) possesses enormous potential to benefit the manufacturing industry. Presently, rotary draw bending (RDB) is one of the most commonly used cold-forming industrial process for bending metal tubes. Pressure die is a fundamental forming tool in RDB processes, and it is conventionally made by various grades of comparatively expensive alloy steels. This research presents a novel design of a pressure die which can be 3D printed by using inexpensive polymeric filaments. In this research paper, the 3D-printed pressure die is named as “FFF-pressure die.” The material used to fabricate the FFF-pressure die is a thermoplastic polymer known as “ecoPLA.” The mechanical properties of ecoPLA are studied in relation to the process conditions of a RDB process. Firstly, an initial feasibility of using the FFF-pressure die in a RDB process is obtained by conducting a quick static stress analysis with actual process conditions. After initial feasibility, a complete RDB process is developed and simulated with actual process conditions and material properties. The FFF-pressure die is then practically fabricated by FFF 3D printer and experimentally tested on an industrial RDB machine. The results of practical experiments are compared with the simulation results. In order to make a comparison of the FFF-pressure die with the conventional metal pressure die, the simulation and practical process is also conducted with the conventional metal pressure die. A performance and cost comparison is made between the polymeric FFF-pressure die and the conventional metal pressure die. Von Mises stresses, contact forces, failure risk, and elastic deformations are analyzed. The advantages and limitations of using the FFF-pressure die in a RDB process are discussed in the end. This research intends to widen the avenue of using cost-effective and lightweight forming tools in metal forming industries.